Breast cancer in patients with germline TP53 pathogenic variants have typical tumour characteristics: the Cohort study of TP53 carrier early onset breast cancer (COPE study). (23rd May 2019) - Packwood, Kate; Martland, Guy; Sommerlad, Matthew; Shaw, Emily; Moutasim, Karwan; Thomas, Gareth; Bateman, Adrian C; Jones, Louise; Haywood, Linda; Evans, D Gareth; Birch, Jillian M; Alsalmi, Ohud A; et al.
Abstract: Germline TP53 pathogenic variants are rare but associated with a high risk of cancer; they are often identified in the context of clinically diagnosed Li–Fraumeni syndrome predisposing to a range of young onset cancers including sarcomas and breast cancer. The study aim was to conduct a detailed morphological review and immuno‐phenotyping of breast cancer arising in carriers of a germline TP53 pathogenic variant. We compared breast cancers from five defined groups: (1) TP53 carriers with breast cancer ( n = 59), (2) early onset HER2‐amplified breast cancer, no germline pathogenic variant in BRCA1/2 or TP53 ( n = 55), (3) BRCA1 pathogenic variant carriers ( n = 60); (4) BRCA2 pathogenic variant carriers ( n = 61) and (5) young onset breast cancer with no known germline pathogenic variant ( n = 98). Pathologists assessed a pre‐agreed set of morphological characteristics using light microscopy. Immunohistochemistry (IHC) for HER2, ER, PR, p53, integrin alpha v beta 6 (αvβ6) integrin, α‐smooth muscle actin (α‐SMA) and pSMAD2/3 was performed on tissue microarrays of invasive carcinoma. We confirmed a previously reported high prevalence of HER2‐amplified, ductal no special type invasive breast carcinoma amongst known TP53 germline pathogenic variant carriers 20 of 36 (56%). Furthermore we observed a high frequency of densely sclerotic tumour stroma in cancers from TP53 carriers (29/36, 80.6%) when compared with non‐carriers, 50.9% (28/55), 34.7% (50/144), 41.4% (65/157), 43.8% (95/217) in groups 2–5 respectively. The majority of germline TP53 gene carrier breast tumours had a high intensity of integrin αvβ6, α‐SMA and pSMAD2/3 expression in the majority of cancer cells. In conclusion, aggressive HER2 positive breast cancers with densely sclerotic stroma are common in germline TP53 carriers. High levels of αvβ6 integrin, α‐SMA and pSMAD2/3 expression suggest that the dense stromal phenotype may be driven by upregulated transforming growth factor beta signalling.